Velocity diagrams : (Music:MCPS) (Engineering mechanics ;, 1991)
Summary: Velocity diagrams are an important tool in helping to solve problems in engineering. After an illustrative case of two vehicles approaching a cross-roads, some examples of engineering mechanisms are presented and analysed.